“A COMPARATIVE STUDY OF ACETIC ACID V/S CIPROFLOXACIN TOPICAL EAR DROPS IN ACHIEVING DRY EAR IN TUBOTYMPANIC CSOM PATIENTS.” - Dr. Navin Agrawal; Dr. Chhavi Agrawal; Dr. Akshita Bhargava; Dr. Harsh Dudhat; Stuti Saraswat; Dr. Rohit Maheshwari; Dr. Arsh Jodhawat; Dr. Ashish Yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aim: To study the effect of topical instillation of ACETIC ACID V/S CIPROFLOXACIN EAR DROPS in medical management of tubotympanic CSOM.Materials and Methods: 100 patients including Male and Female above 15 years attending ENT OPD, at Index Medical College and having perforation in pars tensa (tubotympanic CSOM) will be evaluated. These patients underwent ENT examination. Oto-endoscopic examination was done. Further, patient were advised to undergo X-ray bilateral mastoid and pure tone audiometry.Results: The results of the present study showed that dry ear was significantly achieved in patients using acetic acid (92% patients) than ciprofloxacin (66% patients) ear drops.Conclusion: Medical management of tubotympanic type of CSOM is better achieved using 2% acetic acid ear drops rather than 0.3% ciprofloxacin ear drops.